Transmission studies with Cassava brown streak Uganda virus (Potyviridae: Ipomovirus) and its interaction with abiotic and biotic factors in Nicotiana benthamiana - Ogwoka, Emmanuel; Patil, Basavaprabhu L.; Alicai, Titus; Fauqueta, Claude M. (Journal of Virological Methods, 2010)
Cassava brown streak disease (CBSD), caused by two distinct species, Cassava brown streak Uganda virus (CBSUV) and Cassava brown streak virus (CBSV), is a major constraint to cassava (Manihot esculenta Crantz) production in Africa. Absence of infectious clones of CBSUV or CBSV and the lack of efficient means of mechanical transmission of CBSD has hampered laboratory studies of this disease. Mechanical transmission, achieved mainly by plant sap inoculation, is a widely used technique for characterizing plant viruses. Efficient sap transmission of CBSUV/CBSV to the common laboratory host Nicotiana benthamiana is essential for both basic and applied studies of the virus. We report here the development of an efficient protocol for sap transmission of CBSUV to N. benthamiana and N. debneyi. Several factors affecting transmission efficiency were identified such as the effects of buffer composition, antioxidants, inoculum concentration, plant age and temperature. Higher temperatures (30 ◦C) favored rapid symptom initiation compared to lower temperatures (21 ◦C) when sap prepared in phosphate buffer of pH 7.0 was applied on the leaves of N. benthamiana dusted with the abrasive (carborundum). We demonstrated the usefulness of the transmission method in transient evaluation of CBSUV[UG:Nam:04]-derived RNA interference constructs for CBSD resistance and also in studying the interaction of CBSUV[UG:Nam:04] with cassava mosaic geminiviruses, another important group of viruses infecting cassava.
Keywords: Cassava brown streak virus; Potyviridae; Ipomovirus; Sap inoculation; Synergism; Transient studies